System of Financing of Local Self-Government in the Republika Srpska: Challenges and Contradictions - Marković, Goran; Marilović, Đorđe (NBP. Nauka, bezbednosti, policija, 2025)
The purpose of the work is to analyse the system of financing of local self-government in the Republika Srpska. The realization of the local self-government depends, among other things, on the financial autonomy of the units of local self-government. Financial autonomy is directly interconnected with the possibility of units of local self-government to exercise their competencies. The authors analyse the legal framework of the local self-government and the budgetary system of the Republika Srpska to understand the contradictions, deficiencies, and possible solutions for improvement of the system of financing of the local self-government. One of the main conclusions is that the constitutional provisions on local self-government are so general and poor that they enable the legislator to prescribe any system of local self-government as well as to increase or decrease the financial autonomy of the local communities. Another conclusion is that the units of local self-government are to a considerable extent under the direct or indirect control of the central authorities in two main ways. Firstly, the National Assembly can prescribe by law that some new taxes belong to the local communities or that some existing taxes cease to be their financial resource. Secondly, considerable part of local revenues are taxes which originally belong to the Republika Srpska and which it shares with the local communities according to legally prescribed percentages. One can conclude that legal guarantees of the financial autonomy of the local communities are quite uncertain and under almost total control of the central authorities.
Keywords: Republika Srpska, the Republic of Srpska, Local self-government, Budgetary system, Budget, Financial autonomy.